VITAMIN D AND SEROTONIN’S ROLE IN NEUROPSYCHIATRIC DISORDERS - SARI EKA PRATIWI; FITRI SUKMAWATI (PSGA LP2M IAIN Pontianak, 2020)
Abstract Vitamin D is known to play an active role in the development of nerve cells, as well as regulating the expression of one of the important genes in serotonin metabolism, namely THP2. Vitamin D and serotonin play an important role in the development of various neuropsychiatric diseases, Autism spectrum disorder (ASD), schizophrenia, bipolar disorder, and depression. Method: An article review was carried out by tracing various scientific literature relating to theories regarding the relationship of vitamin D and Serotonin, as well as neuropsychiatric disorders related to metabolic disorders and the production of vitamin D and serotonin. Results: The biological activity of vitamin D is mediated by the vitamin D receptor (VDR). The bonding complex between VDR and VDRE in the promoter of a gene will initiate the transcription process, one of which is TPH2, which plays an active role in the synthesis of brain serotonin. Serotonin has an important role as a neurotransmitter, hormone and morphogen for the brain. This neurotransmitter have important functions in the brain in controlling appetite, energy expenditure, sleep, body temperature, mood, and social cognition. Conclusion: Vitamin D plays an active role in the transcription of TPH2, which plays an active role in the synthesis of brain serotonin. Vitamin D facilitate tryptophan metabolism by increasing TPH2 to synthesize serotonin. Disruption of vitamin D levels will change serotonin levels and function in the brain, resulting in impaired behavior and executive brain function. Keyword: Vitamin D, Serotonin, Autism, Autism Spectrum Disorder